Saprophytic activity of Rhizoctonia in Northeastern Brazilian soils and relationship with physical, chemical and microbiological properties (Research, Society and Development, 2022)
The fungus Rhizoctonia can survive in the soil for long periods without host plants and favorable conditions, almost exclusively in the form of active mycelium and sclerotia, this strategy being called saprophytic colonization. This study aimed to evaluate the saprophytic activity of Rhizoctonia in 52 soil samples from the Northeast region of Brazil and to analyze the relationship between physical, chemical and microbiological properties of soils with this activity. In this study, saprophytic activity was evaluated by baits with segments of cowpea stalks and was detected in 38.5% of the soil samples. There was no significant influence of the type of soil cover at the time of collection and the textural class of soils on the percentage of saprophytic colonization. There were positive and significant correlations (P≤0.01) of the saprophytic activity of Rhizoctonia with the levels of phosphorus (r = 0.80), potassium (r = 0.54) and hydrolytic activity of fluorescein diacetate (r = 0 .51). With these results, it was possible to establish a relationship between the suppressive or conductive potential of some soils and the saprophytism of Rhizoctonia